Literatura Infantojuvenil: compondo um panorama da produção amazonense - Simões, Lucila Bonina Teixeira (2013)
Only very recently, infant literature has become noticeable in the Amazonian culture. The objective of this work is to compose an overview of Amazonian infant literature through a survey of authors and works published in the last thirty years. In order to compose this panorama, first of all it was sought to investigate and reflect on the conception of childhood that determines literary production for children and which of those conceptions are more present in the Amazonian production. For this, besides discussing the evolution of the concept of childhood throughout time, it was sought to assess how this evolution influenced the Brazilian literary production for children and how the Amazonian production stands before this broader scenario. Concurrent with the survey of authors and works of Amazonian infant literature, an archival operation took place and composed an archive of the Amazonian infant literature made up of paratexts of children's books, journalistic texts about the launching of such books and biographic texts. The analysis of these documents, supported by theoretical support of the modern biographical critique and by the studies of Gerard Genette about editorial paratexts, aimed at identifying the arguments of the legitimation discourse on the nascent Amazonian infant literature and on the notion of childhood underlying the project of infant literature that has been brought forward in the Amazon. The study that has been carried out shows the predominance of pedagogical trend in regional books, resulting from a conservative conception of childhood. Lastly, the final part of the paper presents the Dictionary of Amazonian Infant Literature as a product of the research and concrete manifestation of the panorama that this work was proposed to do. KEY WORDS: dictionary; Amazonian literature; infant-juvenile literature